Language Development and Acquisition 2.5 Year Old Child - Sigit Andi Prasetya Dinata; Helmi Seftiani; Mochamad Bintang Priska (Universitas Sebelas Maret, 2022)
This study aims to explain the development and acquisition of language in children aged 2.5 years using qualitative methods. Qualitative methods are used by analyzing and collecting non-numerical data. This study collected data through direct observation, listening, and speaking. The data obtained consisted of primary and secondary data. Primary data came from the subjects studied directly from the observation, listening, and speaking phases; secondary data came from people around the subjects studied. Jenar Azmya Dzulhijjah's speech was the subject of the study. The results of the study showed that children had acquired various types of speech, such as occurrence, consonant substitution, consonant deletion, and word truncation. There are speeches that can be pronounced correctly, correctly, and clearly, but there are also speeches that cannot be pronounced correctly.